PENGARUH EDUKASI KESEHATAN DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN PRAKONSEPSI PADA REMAJA PUTRI - Rakhmawati, Nur; Hidayati , Dania Rofi' Atul; Mardiyah, Siti (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Introduction: Premarital sex among adolescents leads to unplanned pregnancies. Pregnant adolescents aged 10-19 years have a higher risk of eclampsia, endometriosis, systemic infections, and undergoing abortion. Adolescents require reproductive health education, particularly related to preconception, to increase knowledge about pregnancy preparation using appropriate, interesting, and easily accessible media, such as video. Aims: The aim of this study is to find out the influence of health education using video media on preconception knowledge in female adolescents in SMA Muhammadiyah 1 Sragen. Methods: The type of study was quantitative using a pre-experimental method with a one-group pre-test and post-test design. The population of the study was 245 respondents. The sampling technique used was purposive sampling with 71 respondents. The instrument of the study was a preconception knowledge questionnaire, which has been tested for its validity and reliability. Results: The results of the study showed that the average age of respondents was 17 years old. Before receiving health education using video media, 47 respondents (66,2%) had a moderate knowledge level, and after health education using video media, 63 respondents (88,7%) had a good knowledge level. This shows that video media has proven to be effective as an educational tool in increasing adolescent girls' understanding of preconceptions. The results of the Wilcoxon test showed a p-value of 0,000 (p-value<0,05). Conclusion: The results of the analysis showed that there is an influence of health education using video media on preconception knowledge in female adolescents in SMA Muhammadiyah 1 Sragen.